Capabilities accumulation and development: What history tells the theory - Giovanni Dosi; Xiaodan Yu (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
In this contribution we offer a broad overview of the technological, institutional and policy dynamics associated with the great transformation - borrowing Karl Polanyi (1944) expression - leading from traditional, mostly rural, economies to economies driven by industrial activities (and nowadays also advanced services), able to systematically learn how to implement and eventually how to generate new ways of producing and new products under conditions of dynamic increasing returns. Such a "great transformation" entails a major process of accumulation of knowledge and capabilities, both at the levels of individuals and organizations. Certainly, part of such capabilities builds on education and formally acquired skills (what in the economists' jargon often goes under the heading of `human capital'). However, at least equally important, capabilities have to do with the problem-solving knowledge embodied in organizations - concerning e.g. production technologies, the technical and social division of labor, labor relations as well as "dynamic capabilities" of search and learning. In turn, the rates and directions of knowledge accumulation during the catch-up process and the ensuing effects upon the patterns of production and trade are shaped by the economic and institutional framework in which such processes are embedded.
Keywords: 330; catching-up; capability accumulation; innovation; development; Great Transformation